Cross Breeding Hariana Cattle. Abortions and Secondary Sex Ratio - Tomar, S S; Singh, Narinder (Annals of Arid Zone, 2016)
Hariana cows were bred to Hariana, Brown Swiss,Holsteitl Friesian and Danish Red bulls. Records wereanalysed for determining the influence of sires on the incidenceof abortions and frequency of male and female births. It wasobserved that: 1, The overall ratio of male to female birthsin Hariana cows bred to Hariana bulls was higher but thisdifference was not statistically significant. 2. Breeding ofHariana cows wilh bulls of exotic breeds did not change thesex ratio. 3 The incidence of abortions in Hariana cowsbred to Hariana bulls was only 1.1 per cent. 4. The rate ofof abortions were higher in cows bred to exotic bulls, ascompared to Hariana bulls.